2006
DOI: 10.1021/jf052505k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Lipase Activity in Hydrolysis and Acyl Transfer Reactions of Two Latex Plant Extracts from Babaco (Vasconcellea × Heilbornii Cv.) and Plumeria rubra:  Effect of the Aqueous Microenvironment

Abstract: The enzymatic properties of Plumeria rubra latex have been evaluated for the first time, showing a high activity in both hydrolysis and synthesis reactions, and compared to the biocatalytic behavior of babaco (Vasconcellea x Heilbornii cv.) latex. Both biocatalysts have been optimized by studying the various parameters that influence reaction kinetics. The optimum temperatures for hydrolysis reactions were 50 and 55 degrees C for babaco and Plumeria, respectively. The optimum pH for babaco latex was 7, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Besides other factors (e.g., temperature, catalyst concentration, substrate concentration), pH is also an important influencing factor in the stability of enzymes. Extremely low or high pH values probably result in complete or partial deactivation for most enzymes . In our study, k ob –pH profiles in Fig.…”
Section: Resultssupporting
confidence: 47%
“…Besides other factors (e.g., temperature, catalyst concentration, substrate concentration), pH is also an important influencing factor in the stability of enzymes. Extremely low or high pH values probably result in complete or partial deactivation for most enzymes . In our study, k ob –pH profiles in Fig.…”
Section: Resultssupporting
confidence: 47%
“…The biocatalytic activity in terms of lipase activity in hydrolysis and acyl transfer reactions of latex was compared with that of babaco (Vasconcellea x Heilbornii Cv.) (Cambon et al, 2006). Six compounds such as four iridoids, fulvoplumierin, allamcin, allamandin and plumericin; 2,5-dimethoxy-p-benzoquinone and lignan liriodendrin were isolated from different extracts of the plants all showing toxicity to murine lymphocytic leukemia and various human cancer cell-lines (breast, colon, melanoma, lung, fibrosarcoma, KB) (Kardono et al, 1990).…”
Section: Pharmacologymentioning
confidence: 99%
“…Carica pentagona), native to the subtropical mountains of Equator, contains a latex similar to that found in Carica papaya (Kyndt et al 2005). In previous studies, its latex was shown to exhibit biocatalytic activities and the effect of the aqueous microenvironment on the synthesis activity has been evaluated (Cambon et al 2006). In this work, the typo-, regioand stereo-selectivities of crude babaco latex lipase were studied in both aqueous and organic solvents, in hydrolysis and acyltransfer reactions, and compared to those of papaya latex.…”
Section: Introductionmentioning
confidence: 99%